Customer Interest in Saving with Easy Mobile Banking to Support Green Marketing - Ekaputri, Alya Maherka; Dani, Akhmad Nur; Sukresna, I Made; Indriani, Farida (LifeSciFi, 2024)
This study aims to analyze the significance of influence between display design, trust, and easy on customer interest in using mobile banking to support green marketing. The problem is increasing in QRIS transaction volumes in Central Java in 2023 by 301.70%, in addiction mobile banking has an impact on increasing e-commerce transactions by 10.66%. This can reflect the wishes of customers with bank operations at all times using fully digital. A drastic increase will have an impact on the continuity of banking operations and risks. The data used are primary data using questionnaires. The population in 8this study is all banking customers who use mobile banking. Sample in research is all customers domiciled in Semarang, with the age of over 20 years old who use mobile banking with purposive sampling techniques. The analysis model of multiple linear regression analysis test is processed SPSS 25.00. The results of and discussion show that design, trust, and convenience simultaneously have a significant effect on customer interest in using mobile banking in supporting green marketing. While convenience partially has a significant effect on customer interest in using mobile baking in supporting green marketing.